Implementasi Routing Static Pada Wireless Sensor Network Menggunakan Modul Komunikasi LoRA - Nuril Huda; Primantara Hari Trisnawan; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
In Wireless sensor network (WSN) technology, devices or devices that can support wireless networks in WSN are needed, one of which is LoRa. The device is a wireless communication technology that can be used over long distances and has a low power consumption using the radio spectrum in its communication. By default, there is still a problem with these devices that is LoRa communicate with each other directly in just one hop. To overcome this problem routing protocols will be implemented in it to enable multi-hop application. The routing protocol used is static routing, because it is efficient when applied to small scale networks and the processing load on the routing is smaller. The results of performance testing are based on three predetermined test parameters namely Association Time, Packet Loss, and Packet Delivery Ratio (PDR). The value of the highest association time is when sending to sensor node 4 which is the furthest node with an association time value of 0.614 seconds, because to go to that node needs to go through 2 other nodes. Then in the Packet Loss test the highest percentage value is 8%. The last test Packet Delivery Ratio obtained the lowest value of 92%. From the above data it can be concluded, the large number of nodes that are traversed makes the performance of the system reduced.